KUALITAS REPAIR WELDING MENGGUNAKAN METODE PENGELASAN TIG DENGAN PERLAKUAN PREHEATING DAN POST WELD HEAT TREATMENT PADA CAST WHEEL ALUMINIUM - Dewi Rima Ratri Siwi; Budi Harjanto; Nyenyep Sriwardani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The Purpose of this research are to know chemical composition, find micro structure, find impact strength, find speciment’s hardeness level on allumminium cast wheel before and after Tungsten Inert Gas welding. The speciment on this research is aluminum cast wheel or aluminum velg. The data analysis on this research is a comparative descriptive method, that the observation result is analyzed by description. And then compare the observation result between the data before TIG welding or before conducted preheating and PWHT. The parameter of analyze data are included: the testing of chemical composition, microstructure, hardness and impact. Based on the result of this research, it can be concluded that the cast wheel material is aluminum type cast alloy AA.445.2 which has non-heat treatable characteristic. The research results show that the microstructure of Al grain in the HAZ region fused with primary aluminum (α-Al) and grain Si alloy formed between the primary α-Al. The impact strength value on the welded speciment is higher than impact strength value before welding those are 0.0616 J/mm2 and 0.0384 J/mm2. Hardeness level on the speciment before welding processes is 103,381 VHN. The number is higher than after on the welding area, the hardeness level is lower too that is 44,051 VHN, whereas the hardeness level an the HAZ is a 37,943 VHN and 35,465 VHN on the base material.